2019
DOI: 10.15252/emmm.201910659
|View full text |Cite
|
Sign up to set email alerts
|

The novel BET‐CBP/p300 dual inhibitor NEO2734 is active in SPOP mutant and wild‐type prostate cancer

Abstract: CULLIN3‐based E3 ubiquitin ligase substrate‐binding adaptor gene SPOP is frequently mutated in prostate cancer (PCa). PCa harboring SPOP hotspot mutants (e.g., F133V) are resistant to BET inhibitors because of aberrant elevation of BET proteins. Here, we identified a previously unrecognized mutation Q165P at the edge of SPOP MATH domain in primary and metastatic PCa of a patient. The Q165P mutation causes structural changes in the MATH domain and impairs SPOP dimerization and substrate degradation. Different f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 46 publications
0
60
0
Order By: Relevance
“…The PC organoids expressing SPOP W131R mutation are resistant to intrinsic BET inhibitors-induced cell growth arrest and apoptosis due to the stabilization of BET protein and activation of AKT-mTORC1 signaling [124][125][126]. To overcome this resistance, Yan et al have investigated the anti-cancer effects of NEO2734 (novel BET-CBP/p300 dual inhibitor) in SPOP-mutated organoids from PC patients [127]. They demonstrated that NEO2734 showed the effectiveness in BET inhibitor (JQ1)-resistant SPOP mutant PC organoids [127].…”
Section: Pc Organoids For Predicting Anti-cancer Drugs Sensitivity Ormentioning
confidence: 99%
See 1 more Smart Citation
“…The PC organoids expressing SPOP W131R mutation are resistant to intrinsic BET inhibitors-induced cell growth arrest and apoptosis due to the stabilization of BET protein and activation of AKT-mTORC1 signaling [124][125][126]. To overcome this resistance, Yan et al have investigated the anti-cancer effects of NEO2734 (novel BET-CBP/p300 dual inhibitor) in SPOP-mutated organoids from PC patients [127]. They demonstrated that NEO2734 showed the effectiveness in BET inhibitor (JQ1)-resistant SPOP mutant PC organoids [127].…”
Section: Pc Organoids For Predicting Anti-cancer Drugs Sensitivity Ormentioning
confidence: 99%
“…To overcome this resistance, Yan et al have investigated the anti-cancer effects of NEO2734 (novel BET-CBP/p300 dual inhibitor) in SPOP-mutated organoids from PC patients [127]. They demonstrated that NEO2734 showed the effectiveness in BET inhibitor (JQ1)-resistant SPOP mutant PC organoids [127].…”
Section: Pc Organoids For Predicting Anti-cancer Drugs Sensitivity Ormentioning
confidence: 99%
“…Because SPOP targets various oncogenic substrates (e.g., AR, DEK, TRIM24, NCOA3, BRD2, and BRD4), accumulation of these oncogenic proteins contributes to tumor formation in the prostate [ 52 ]. Another prostate cancer-associated mutation of SPOP, Q165P at the edge of the MATH domain, impairs dimerization of SPOP, resulting in the inhibition of substrate degradation [ 53 ].…”
Section: Molecular Properties Of Spopmentioning
confidence: 99%
“…NEO2734 has been recently demonstrated as a multi-bromodomain inhibitor which targets BRD2, BRD3, BRD4, CBP and p300 (Yan et al, 2019). We examined the efficacy of NEO2734 in overcoming PI3K/AKT resistance.…”
Section: Bet and Cbp/p300 Bromodomain Dual Inhibitor Neo2734 And Butymentioning
confidence: 99%
“…NEO2734 (also known as EP31670) was identified from a drug discovery collaboration between the University of Miami, Epigenetix Inc and the Neomed Institute (Yan et al, 2019). The activity of NEO2734 in inhibition of the bromodomains in BET and CBP/p300 was initially tested with the BROMOscan platform (DiscoverX/Eurofins).…”
Section: Multi-bromodomain Inhibitor Neo2734mentioning
confidence: 99%